Shape-controlled synthesis of nickel phosphide nanocrystals and their application as hydrogen evolution reaction catalyst. (May 2015) - Li, Hua; Wang, Wenzhong; Gong, Zhaoyuan; Yu, Yanmin; Piao, lijin; Chen, Huiying; Xia, Jianxin
Abstract: Monodisperse nickel phosphide (Ni2 P) nanorods and nanoparticles were synthesized by one step solution-phase route, in which the mixture of trioctylphosphine oxide (TOPO) and trioctylphosphine (TOP) was used as solvent, capping agent and phosphor source. The morphologies of the Ni2 P nanocrystals were controlled simply by varying the dropping rate of metal source. The as-prepared Pt-free Ni2 P nanocrystals exhibit the enhanced electrocatalytic activity toward hydrogen evolution reaction (HER) compared to pure commercial Ni nanoparticles. Therefore, the obtained Ni2 P nanocrystals appear to be promising non precious metal electrocatalysts for HER. Highlights: Monodisperse Ni2 P nanorods and nanoparticles were synthesized in a single step process using a solution-phase route. The morphology of the produced nickel phosphide structures was controlled simply by varying the dropping rate of metal source. Such Pt-free nanocrystals exhibit electrocatalytic activity toward hydrogen evolution reaction (HER) and appear to be promising electrocatalysts for HER.